The Effect of Political Law on the Development of the Police of the Republic of Indonesia - Edi Saputra Hasibuan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
As an independent country and has sovereignty, Indonesia is certainly equipped with security functions, both military (TNI) and law enforcement (Polri). The two of them used to be united in one institution called ABRI (Indonesian Armed Forces), the institution was led by the Minister of Defense and Security as well as the Commander of the Armed Forces, after the Suharto leadership stepped down, there was a separation between the TNI, both land, sea and air forces and the Police. Of course, there were many factors that influenced the separation of the two institutions, one of which was related to the legal politics that occurred at that time, the transfer of top leadership gave different policies and views on an institution and other state apparatus. The National Police itself has experienced changes from time to time, starting from the style of law enforcement, authority, to the vision and mission of the Police. The presence of the study of legal politics provides a new color and understanding in seeing law as a product of political power resulting from a long process, both negotiation and contestation of interests that work through the process of law formation.